Eco-friendly baker’s yeast for Microbial Enhanced Oil Recovery (MEOR) / Mohd Sabri Zulkifli … [et al.] - Zulkifli, Mohd Sabri; Abdul Manaf, Shareena Fairuz; Tengku Mohd, Tengku Amran; Ghazali, Nurul Aimi; Alias, Nur Hashimah (Research Innovation Business Unit, 2014)
The oil and gas industry contribute significantly to Malaysia’s economy growth. Besides that, PETRONAS expects the implementation of improved oil recovery (IOR) and enhanced oil recovery (EOR) projects to contribute 150,000 barrels per day to the domestic production by 2020. It is said that IOR and EOR technologies had improved oil recovery to between 40 and 50 per cent from 35 per cent on average in oilfields using traditional methods. PETRONAS also claimed that the increase in recovery will give Malaysia another two billion barrels of oil because presently there are 20 billion barrels of oil in place in Malaysian reservoirs. Besides improving oil recovery factor, IOR and EOR projects also help arrest the declining production of maturing oilfields. Currently, oil production in Malaysia stands at 500,000 barrels per day, down from 650,000 barrels per day during its peak in the 90s. On EOR projects, PETRONAS currently has identified 14 fields to be implemented with EOR technology. Of these, there are three projects had been approved, including Tapis field offshore East peninsular which was scheduled to produce its first oil early next year. Other projects are Baronia oilfield and Betty oilfield which are located at offshore Sarawak, both oilfields are expected to start producing oil using EOR technology by 2017 and 2018 respectively. EOR is a tertiary recovery method used to increase the oil mobility in order to produce oil at optimum oil recovery which cannot be achieved by primary and secondary oil recovery. However, the commercial chemicals used in EOR may harm the environment. Hence, these environmental concerns lead to the development of microbial enhanced oil recovery (MEOR). MEOR used a biological approach that utilizes the microbes in order to improve oil recovery and MEOR is eco-friendly to marine environment because the microbes produced biodegradable cellular products. Changqing field in China, Piedras Coloradas field in Argentina and Bokor field in Malaysia are some of success MEOR pilot projects. Particularly, Saccharomyces Cerevisiae microbe obtained from baker’s yeast can successfully be applied in MEOR. The carbon dioxide and ethanol produced from fermentation of Saccharomyces Cerevisiae able to enhance the oil recovery. Saccharomyces Cerevisiae is a species of yeast that is classified in fungi domain. In this study, the fermentation of Saccharomyces Cerevisiae was done using yeast extract and glucose with continuous supply of carbon and nitrogen sources to produce carbon dioxide and ethanol. The Saccharomyces Cerevisiae grows rapidly during the fermentation process which was completed in 14 hours with 6 hours lag phase and the result showed that, glucose concentration decreased as the ethanol and carbon dioxide concentration increased. Besides that, the flooding experiment was performed to measure the percentage of oil recovery using sand pack flooding rig and Saccharomyces Cerevisiae was injected into and grown in the sand pack. The result showed that the Saccharomyces Cerevisiae degrade the long-chain alkane and improve the ration between short chain alkane and long-chain alkane concentrations of oil in the sand pack. These leads to an improvement in oil water mobility ratio, decrease in viscosity of the oil and finally improves the oil sweep efficiency and enhanced the oil recovery. In conclusion, Saccharomyces Cerevisiae is most suited for MEOR as it is friendly to the environment, non-hazardous and safe for marine life. This new innovation can lead to the cost effective EOR project which offers a safe commercial method that can help government increase our nation’s energy production by reducing dependence on imported oil